Color bias in children revisited: findings from Portugal - Félix Neto (1997)
Earlier studies of preschool children in the United States, Western Europe and Asia have demonstrated a bias favoring the color white relative to the color black, and a bias favoring light-skinned human figures relative to dark-skinned figures. In this study, procedures used in previous studies were translated and administered to five- and eight-year-old children in Portugal. Both types of bias were found among the Portuguese children providing additional evidence that the pro-white and pro-light-skinned biases are pancultural tendencies. The biases were not different by gender, but they were higher among eight-year-old children than five-year-olds children and, hence, seemed more likely to be attributable to cultural learning.